Parametric comparison of multicast support for network mobility management: A qualitative analysis - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Abdullah, Azween; Mohd. Ramli, Huda Adibah; Islam, Shayla (Science and Engineering Research Support Society, 2016)
Proxy Mobile IPv6 (PMIPv6) was initially introduced to assist unicast network-based mobility. In recent years, new approaches have been introduced to provide multicast support in PMIPv6. IP multicast is an imperative mechanism for internet video provision. As the usage of internet data traffic remains to develop rapidly, there is a need to optimize and improve the performance of multicast service. Issues such as large overhead, high packet loss rate, single point of failure, service disruption time, handover latency, and non-route optimization needs to be tackled efficiently. To provide multicast services in PMIPv6, route optimization, global mobility, load balancing and context transfer approaches have been introduced. The foremost aim of this paper is to study and analyze these methods via qualitative analysis. This is to focus the advantages and the limitations of the current approaches.